Nicorandil Improves Left Ventricular Myocardial Strain in Patients With Coronary Chronic Total Occlusion - Chen, Shaomin; Ma, Chen; Feng, Xinheng; Cui, Ming (Frontiers in Cardiovascular Medicine, 2022)
Background Nicorandil is recommended as a second-line treatment for stable angina; however, randomized-controlled trials to evaluate the benefit of nicorandil for patients with chronic total occlusion (CTO) are lacking. Objective To determine whether nicorandil can improve left ventricular myocardial strain in patients with CTO. Methods Patients with CTO were included and randomized to the nicorandil group (n = 31) and the control group (n = 30). Nicorandil was given orally at 15 mg/day for 3 months in the nicorandil group. Three-dimensional-speckle tracking echocardiography and the Seattle Angina Questionnaire (SAQ) survey were performed at baseline and at 3 months. The primary study endpoint was the left ventricular (LV) global area strain (GAS) at 3 months. Results The nicorandil group and the control group were well matched at baseline, including the mean GAS and SAQ scores. At 3 months, GAS in the nicorandil group was significantly higher than that in the control group (−23.7% ± 6.3% vs −20.3% ± 5.6%, respectively; P=0.033). There were no significant differences in LV global longitudinal strain, global circumferential strain, global radial strain, LV ejection fraction, LV end-diastolic volume, and LV end-systolic volume at 3 months between the two groups. At 3 months, the SAQ scores for angina stability, angina frequency, and treatment satisfaction in the nicorandil group were significantly higher than those in the control group. Conclusion Nicorandil treatment can improve GAS and angina symptoms in CTO patients.